2013
DOI: 10.1123/jsep.35.2.156
|View full text |Cite
|
Sign up to set email alerts
|

An Attachment Theory Perspective in the Examination of Relational Processes Associated With Coach-Athlete Dyads

Abstract: The aim of the current study was to examine actor and partner effects of (a) athletes' and coaches' attachment styles (avoidant and anxious) on the quality of the coach-athlete relationship, and (b) athletes' and coaches' quality of the coach-athlete relationship on relationship satisfaction employing the actor-partner interdependence model (Kenny, Kashy, & Cook, 2006). Coaches (N = 107) and athletes (N = 107) completed a questionnaire related to attachment styles, relationship quality, and relationship satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Another pivotal improvement in the PSISS-2 was the attempt to include affiliation and dysfunction to represent the unconditional aspects of social influence that are well-documented psychology literature. 50,53,75 The findings from Study 2 supported only dysfunction as an independent psychosocial construct, which concurs with existing literature about the presence of unconditional negative social influence in sport, such as antisocial behaviour [43][44][45] and bullying/victimization. 7,46 It may imply that young athletes are able to differentiate unconditional negative social influence (ie, dysfunction) from conditional negative social influence (ie, punishment for mistakes or poor performance), as punishment could have an adaptive role on young athlete when it is perceived as constructive feedback.…”
Section: Conditional and Unconditional Responsesupporting
confidence: 87%
See 1 more Smart Citation
“…Another pivotal improvement in the PSISS-2 was the attempt to include affiliation and dysfunction to represent the unconditional aspects of social influence that are well-documented psychology literature. 50,53,75 The findings from Study 2 supported only dysfunction as an independent psychosocial construct, which concurs with existing literature about the presence of unconditional negative social influence in sport, such as antisocial behaviour [43][44][45] and bullying/victimization. 7,46 It may imply that young athletes are able to differentiate unconditional negative social influence (ie, dysfunction) from conditional negative social influence (ie, punishment for mistakes or poor performance), as punishment could have an adaptive role on young athlete when it is perceived as constructive feedback.…”
Section: Conditional and Unconditional Responsesupporting
confidence: 87%
“…Another pivotal improvement in the PSISS‐2 was the attempt to include affiliation and dysfunction to represent the unconditional aspects of social influence that are well‐documented psychology literature . The findings from Study 2 supported only dysfunction as an independent psychosocial construct, which concurs with existing literature about the presence of unconditional negative social influence in sport, such as anti‐social behaviour and bullying/victimization .…”
Section: Discussionsupporting
confidence: 72%
“…Subsequent studies have extended Davidovitz et al's [95] findings to business organizations, showing that managers' responsiveness contributes positively to workers' job satisfaction, organizational commitment, and psychological well-being [96][97][98]. These findings were conceptually replicated in studies examining relationships between school directors and teachers [99] and between coaches and athletes [100]. Using an experimental manipulation of supervisor behavior, Game [101] found that less secure workers reacted to a manager's cold and rejecting behavior with greater distress.…”
Section: Leadership and Managementmentioning
confidence: 79%
“…This early work exploring the dynamics of the coachathlete relationship greatly emphasised leadership behaviour (Lafrenière, Jowett, Vallerand, & Carbonneau, 2011). Now however, the literature has progressed to using theories to understand the relationship between coach and athlete as an outcome of reciprocal and interpersonal behaviours, cognitions and emotions such as theories of social exchange (Poczwardowski, Barott, & Henschen, 2002), motivation (Mageau & Vallerand, 2003), and interpersonal as well interdependency theories (Davis, Jowett, & Lafrenière, 2013;Jackson, Dimmock, Gucciardi, & Grove, 2011;Lorimer, 2011) . This emphasis on interpersonal behaviours has suggested athletes' needs are primarily trust, respect, communication, commitment, automony and empowerment (Jowett, 2006;Jowett & Poczwardowski, 2007;Kidman, Thorpe, & Hadfield, 2005;Lafrenière et al, 2011;Mageau & Vallerand, 2003).…”
Section: Introductionmentioning
confidence: 99%